Puerarin Promotes the Migration and Differentiation of Myoblasts by Activating the FAK and PI3K/AKT Signaling Pathways - Xiaofeng Fang; Hangjia Xu; Zhaoxin Fan; Hongge Yang; Yan Huang; Lin Xu; Yiwei Rong; Wei Ma; Liubao Pei; Hongsheng Liang (Biology)
Puerarin, a flavonoid compound present in the roots of radix puerariae, contributes to the development of tissues such as bone and nerve, but its role in skeletal muscle regeneration remains unclear. In this study, we employed C2C12 myoblasts and barium chloride (BaCl2)-based muscle injury models to investigate the effects of puerarin on myogenesis. Our study showed that puerarin stimulated the migration and differentiation of myoblasts in vitro. For the mechanism study, we found that puerarin’s influence on cell migration was associated with the activation of FAK signaling; additionally, puerarin induced myoblast differentiation by upregulating the PI3K/AKT pathway. We also found that puerarin treatment could improve muscle regeneration following muscle injury. Taken together, our data indicate that puerarin facilitated myogenesis by promoting migration and differentiation, which suggests puerarin as a new candidate drug for the treatment of muscle loss diseases.